Radiopharmaceuticals and the PET probe in the detection of Ductal Carcinoma in situ of the breast - Butler-Henderson, Kerryn Ann (Curtin University, 2014)
The use of a hand-held positron emission tomography (PET) probe during breast surgery can potentially reduce the rate of second operations, having a number of implications. The PET probe tested in ductal carcinoma in situ (DCIS) surgery demonstrated to be 96.5% accurate when compared to pathology. This research examines the current technology available, the epidemiology of DCIS in Western Australia, testing of the radiopharmaceutical used with the probe and the PET probe itself.